Unraveling yield heterosis in Chinese cabbage hybrid by comparative transcriptomic analysis and LHCB1 gene function analysis - Wang, Ruihua; Han, Min; Han, Taili; Xu, Ligong; Li, Yuanyuan (Frontiers in Plant Science, 2025)
BackgroundChanges in gene expression in plant hybrids are closely related to heterosis. Currently, few reports on key genes that promote yield advantage formation in Chinese cabbage hybrids exist.MethodsWe conducted a comparative transcriptomic analysis between a Chinese cabbage hybrid (weichunbaiNo.3) and its parents using RNA sequencing, and the differentially expressed genes between the Chinese cabbage hybrid and its parents were confirmed in the rosette and the mature stages. The expression patterns of the differentially expressed genes were examined. The weighted gene coexpression network analysis and virus-induced gene silencing technology were employed to assess the key gene function in yield advantage formation of the Chinese cabbage hybrid.ResultsIn total, 3652 and 2768 genes were differentially expressed between the Chinese cabbage hybrid and its parents in the rosette and mature stages, respectively. These differentially expressed genes among the hybrid and its parents presented diverse expression patterns, and the expression levels of the most differentially expressed genes in the hybrid were higher than one of the parents but lower than another. The horticultural characteristics showed that weichunbai No. 3 hybrid had a greater yield advantage compared with parents. A vital hub gene related to yield, BraA09g035160.3C (an LHCB1 gene), was identified by weighted gene coexpression network analysis. Through virus-induced gene silencing technology, the expression level of the BraA09g035160.3C gene in the hybrid was dramatically decreased, which slowed hybrid growth.DiscussionBraA09g035160.3C gene could play an important regulatory role in the yield advantage formation of weichunbai No. 3. These results will provide an important reference for in-depth research on the molecular mechanism underlying the yield advantage formation of Chinese cabbage hybrids.